FAKTOR YANG MEMPENGARUHI EARNINGS QUALITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Annah Annah; Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims at how the role of dividend payment, firm size, and family ownership on earnings quality on manufacturing company listed on Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 72 companies. Data processing techniques using multiple regression analysis what helped by Microsoft Office 2013 and Eviews 9.0 software. The results of this stude indicate that dividend payment has a significant and positive influence on earnings quality while firm size and family ownership has insignificant influence on earnings quality. The implication of this study is the company need to pay dividend to their investors to increase earnings quality which will bring a good signal for investors.